2020
DOI: 10.1002/jsfa.10576
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spirulina (Arthrospira platensis) microencapsulated in alginate and whey protein concentrate addition on physicochemical and organoleptic properties of functional stirred yogurt

Abstract: BACKGROUND: Consumption of Spirulina-based functionalized food is usually unpleasant due to its specific sensorial properties. Therefore, Spirulina was encapsulated using alginate and whey protein concentrate (WPC) by emulsification method, and the effect of adding free and microencapsulated Spirulina (MS) to non-fat stirred yogurt was investigated during storage. RESULTS: Scanning electron microscope investigated microcapsules morphology and their mean particle size that was 52 ∼m, and electrostatic interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 42 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…In this study, Spirulina was encapsulated using alginate and whey protein concentrate (WPC) by the emulsification method. It was found that, the particle size of microcapsules was found as 51.73 ± 37.69 lm [31]. In the literature, there is not any study on B. braunii and M. aeruginosa oil extracts loaded nanoparticle production by the electrospraying method.…”
Section: Characterization Of Microalgal Oil Extract Loaded Nanoparticlesmentioning
confidence: 98%
“…In this study, Spirulina was encapsulated using alginate and whey protein concentrate (WPC) by the emulsification method. It was found that, the particle size of microcapsules was found as 51.73 ± 37.69 lm [31]. In the literature, there is not any study on B. braunii and M. aeruginosa oil extracts loaded nanoparticle production by the electrospraying method.…”
Section: Characterization Of Microalgal Oil Extract Loaded Nanoparticlesmentioning
confidence: 98%
“…There are various techniques of encapsulation of juices or concentrates (hydrophilic fillers) into polymers of natural origin and the drip method, in this case, is the most promising [13] Work [14] notes the relevance of the drip method for obtaining capsules but this work is associated with the production of gelatin capsules.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…For the dairy products fortification with microalgae, Spirulina -loaded alginate microcapsules coated with whey protein concentrate were prepared. Microencapsulation improved the acceptance of fortified yogurt, making the color of the final product lighter [ 78 ].…”
Section: Yogurt Fortification With Nano/microencapsulated Bioactive Ingredientsmentioning
confidence: 99%